Photocatalytic Degradation of Remazol Brilliant Blue R and Remazol Yellow FG using TiO2 doped Cd, Co, Mn - Candra Purnawan; Sayekti Wahyuningsih; Oktaviani Nur Aniza; Octaria Priwidya Sari (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
TiO2 and TiO2 doped Cd, Co, Mn (TiO2-M) were synthesized with a sol-gel method, and the photocatalytic activity of Remazol Brilliant Blue R and Remazol Yellow FG has been conducted. TiO2-M (Cd, Co, Mn) was synthesized with the mol Ti:M ratio of 3:1, and the materials were calcined at 300, 400, and 500 °C. The materials were characterized by X-ray Diffraction (XRD), Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDX), and UV-Vis Reflectance. The XRD result shows that at the temperature of 300 °C TiO2 and TiO2-M formed tend to be amorphous. At 400 °C the anatase phase is formed, while at 500 °C the rutile phase begins to form. And overall, the crystallinity of TiO2 is higher than metal-doped TiO2. The UV-Vis Reflectance result showed that the bandgap energy of all doping materials (TiO2-M) decreased. The larger the metal ion radius of dopant, the larger the crystal size obtained  and then the higher the bandgap obtained. The results of SEM-EDX showed that the morphology of TiO2 was spherical and regular, whereas the morphology of TiO2-M had a smoother surface due to the influence of metal doping. Photocatalytic activity of TiO2-M on Remazol Brilliant Blue R and Remazol Yellow FG was greater than TiO2. The optimum pH of the solution was obtained at pH 5 and the optimum catalyst phase was obtained at the anatase phase. The percentages degradation for 30 min of Remazol Brilliant Blue R were 67.34% (TiO2), 92.12% (TiO2-Co), 85.47% (TiO2-Mn), and 83.91% (TiO2-Cd), while for Remazol Yellow FG they were 58.84% (TiO2), 74.61% (TiO2-Co), 67.93% (TiO2-Mn) and 64.19% (TiO2-Cd), respectively. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).